Advancing Accountability through Conselhos Consultivos in Mozambique: PROGOAS Case Study. (17th September 2013) - Faehndrich, Marco; Nhantumbo, Ilídio
Summary: In recent years accountability has become a buzzword in the development agenda. Even though evidence of its impact remains weak, the underlying assumption is that accountability will result in empowerment, improved quality of democratic governance, and development effectiveness. It is therefore a crucial issue for Mozambique, where good governance is widely seen as one of the biggest challenges in the decentralisation process and poverty reduction strategies. This case study explores the possible factors that enable or hinder accountability initiatives in Mozambique, focusing on the Governance, Water and Sanitation Programme (PROGOAS) implemented by Helvetas Swiss Intercooperation (HELVETAS) and co‐financed by the Swiss Agency for Development and Cooperation (SDC). It examines how public and social accountability can be promoted in a fragile context in terms of institutional capacity and legitimacy, and looks at the constraints and opportunities encountered by conselhos consultivos, a recent and promising institution in Mozambique. Based on a survey, several interviews, a power analysis and the authors' personal observations, this study concludes that PROGOAS can advance public accountability at the local level, especially when different approaches, such as capacity building, radio programmes and local governance self‐assessments, are combined and developed. However, public accountability is also influenced by other endogenous variables of local governance, such as functionality, representation, participation in decision making and power relations, which can be addressed only partially by programme activities. No evidence was found that an external actor such as PROGOAS can contribute in the short run to the emergence of sustainable initiatives that manifest themselves through conselhos consultivos . The programme can sow seeds and create a fertile ground, especially through capacity development and dissemination of information. But local civil society is still too fragmented, weak and aid dependent to play an autonomous role. It is therefore likely that citizens will create new political spaces and adopt new forms of power only as a result of increasing decentralisation, public accountability and local development. For this reason, it is suggested that INGOs and national NGOs should play a supporting role at all levels of the political system, creating an enabling environment for accountability from the bottom to the top. In particular, they should embody accountability throughout planning, implementation and monitoring processes by sharing information, knowledge and opinions with stakeholders, beneficiaries and the general public; they should strengthen local organisations and their capacity to hold local authorities more accountable; sensitise local authorities by emphasising incentives for accountability; they should provide an informational bridge between the district level and provincial and national levels; and they should promote institutional change at the centre towards more political, administrative and financial decentralisation.